Autoclaving of ultra‐high performance concrete (UHPC). Issue 4 (1st September 2018) - von Werder, Julia; Simon, Sebastian; Lehmann, Christian; Selleng, Christian; Fontana, Patrick; Meng, Birgit
Abstract: By the combination of an optimized granulometry, a reduced water–cement ratio and the use of superplasticizers ultra‐high performance concrete achieves a compressive strength of over 150 N/mm 2 and a high resistance regarding acids and water‐soluble salts. In different research projects the effect of an autoclavation on the mechanical strength and the phase composition was analyzed. In systematic studies, the concrete mix and the process parameters were varied. The results show that autoclavation leads to an improved pozzolanic and hydraulic reaction and significantly improves the mechanical strength compared to a conventional thermal treatment. If a minimum time‐span for hydration is ensured, the achievable strength level is not dependent on the prestorage time. However, the duration of the autoclaving is significant. After the maximum strength is reached there is only a very slight decrease, even if unrealistically long autoclaving times are applied.